2000
DOI: 10.1021/ie000238w
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carbon Dioxide onto Hydrotalcite-like Compounds (HTlcs) at High Temperatures

Abstract: The adsorption capacities of carbon dioxide on six commercial hydrotalcite-like compounds and the main factors (aluminum content, anion type, water content, and heat treatment temperature) influencing their adsorption capacity at high temperatures have been investigated using a gravimetric technique. There is an optimum aluminum content and heat treatment temperature for the adsorption capacity. The carbonate anion favors adsorption of carbon dioxide compared to OH-, and a low content of water also improves th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
178
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(191 citation statements)
references
References 17 publications
10
178
2
1
Order By: Relevance
“…Among these, solid adsorbents have been commonly fit for the integrated gasification combined cycles (IGCC) related pre-combustion CO 2 capture processes [4,5], e.g., sorption enhanced water gas shift (SEWGS) and sorption enhanced biomass reforming (SEBR) reactions [12][13][14][15]. Among the abundant solid adsorbents which tend to capture CO 2 at moderate temperatures [5,[14][15][16], layered double hydroxides (LDHs) derived metal oxides [17][18][19][20][21] and magnesium oxide (MgO) based compounds [22][23][24][25][26] are promising for the SEWGS and SEBR technologies in the temperature range of 200-400 • C [10,[27][28][29][30]. LDHs have the reputation of outstanding thermal stability and relatively fast CO 2 adsorption kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, solid adsorbents have been commonly fit for the integrated gasification combined cycles (IGCC) related pre-combustion CO 2 capture processes [4,5], e.g., sorption enhanced water gas shift (SEWGS) and sorption enhanced biomass reforming (SEBR) reactions [12][13][14][15]. Among the abundant solid adsorbents which tend to capture CO 2 at moderate temperatures [5,[14][15][16], layered double hydroxides (LDHs) derived metal oxides [17][18][19][20][21] and magnesium oxide (MgO) based compounds [22][23][24][25][26] are promising for the SEWGS and SEBR technologies in the temperature range of 200-400 • C [10,[27][28][29][30]. LDHs have the reputation of outstanding thermal stability and relatively fast CO 2 adsorption kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In the above formula, typically 0.2 e x e 0.33, but LDH with significantly higher x values have also been reported. 4 The most frequently studied LDH is [Mg 1-x Since these materials have a well-defined layered structure with nanometer (0.3-3 nm) interlayer distances and contain important functional groups, they are widely investigated for use as adsorbents for liquid ions [5][6][7] and gas molecules 8,9 and as catalysts for oxidation, [10][11][12] reduction, 13 and other catalytic reactions. [14][15][16] Recently, LDH materials have also been investigated in novel reactive separation processes to increase the conversion of catalytic reactions by removing one of the products from the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [103,[105][106][107][108][109][110][111][112] have investigated CO 2 adsorption on HTs and mixed oxides, but to our knowledge, no HT/mixed oxide membrane studies have been reported. Yong et al [110] have investigated the adsorption of CO 2 onto HT-like compounds at elevated temperatures.…”
Section: Hydrotalcite Membranesmentioning
confidence: 99%
“…Yong et al [110] have investigated the adsorption of CO 2 onto HT-like compounds at elevated temperatures. They observed that the CO 2 adsorption capacity of all HTs higher than 0.30 mmol/g and up to 0.5 mol/kg at 300 °C and 1 bar.…”
Section: Hydrotalcite Membranesmentioning
confidence: 99%